Factors Influencing Tobacco Consumption among 11th Grade Students at Nino Konis Santana Gleno Ermera General Secondary School in 2024 - Jesus Amaral, Isabel de; Costa, Joaninha da; Martins de Jesus, Jelina; Ximenes Martins, Adelina; Deus, Julião de; Faleria Yung, Maria (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Tobacco contains addictive and toxic substances, including tar, nicotine, and carbon monoxide, which adversely affect human health. Timor-Leste has a high prevalence of tobacco use, particularly among youth. Objective: This study aimed to identify factors influencing tobacco use among 11th grade students at Nino Konis Santana General Secondary School, Gleno Ermera. Method: A quantitative cross-sectional design was employed, with 52 students selected through systematic random sampling. Data were collected via questionnaires and analyzed using chi-square tests. Result and Discussion: Univariate analysis showed that 61.5% of students had insufficient knowledge about tobacco, 59.6% held positive attitudes toward avoiding tobacco, 61.5% lived in supportive environments against tobacco use, and 59.6% were current smokers. Bivariate analysis revealed significant associations between tobacco consumption and knowledge (X²=0.000), attitude (X²=0.001), and environmental factors (X²=0.003), all p<0.05. These findings indicate that knowledge, attitudes, and environmental factors significantly influence tobacco use. Conclusion: Interventions should include school smoking policies, health education, and awareness campaigns